2007
DOI: 10.1007/s00425-007-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

cyclo-Oxylipin-galactolipids in plants: occurrence and dynamics

Abstract: cyclo-Oxylipin-galactolipids (cGL) are mono- or digalactosyldiglycerides carrying a cyclo-oxylipin in the sn1- and/or sn2-position or esterified to the galactose moiety. These compounds were recently identified in Arabidopsis thaliana. We provide evidence that cGL are mainly, if not exclusively, part of the thylakoid and can be hydrolysed by lipolytic activities associated with photosynthesis-related protein complexes in vitro. Using HPLC/ESI-mass spectrometry, cGL are shown to be restricted in occurrence to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 49 publications
3
60
0
Order By: Relevance
“…The upregulation of some of these early JA biosynthesis genes in developing pxa1-1 seeds suggests that there might be an increased flux of precursors including OPDA through the JA biosynthesis pathway. A large amount of OPDA and dnOPDA is found esterified in chloroplast galactolipids in Arabidopsis (Stelmach et al, 2001;Hisamatsu et al, 2003Hisamatsu et al, , 2005Andersson et al, 2006;Buseman et al, 2006;Nakajyo et al, 2006;Bö ttcher and Weiler, 2007;Kourtchenko et al, 2007). Stelmach et al (2001) showed that OPDA esterified at the sn1 position in galactolipids could be released by sn1-specific lipases.…”
Section: Accumulation Of Oxylipins In Cts/pxa1 Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of some of these early JA biosynthesis genes in developing pxa1-1 seeds suggests that there might be an increased flux of precursors including OPDA through the JA biosynthesis pathway. A large amount of OPDA and dnOPDA is found esterified in chloroplast galactolipids in Arabidopsis (Stelmach et al, 2001;Hisamatsu et al, 2003Hisamatsu et al, , 2005Andersson et al, 2006;Buseman et al, 2006;Nakajyo et al, 2006;Bö ttcher and Weiler, 2007;Kourtchenko et al, 2007). Stelmach et al (2001) showed that OPDA esterified at the sn1 position in galactolipids could be released by sn1-specific lipases.…”
Section: Accumulation Of Oxylipins In Cts/pxa1 Seedsmentioning
confidence: 99%
“…Dinor-oxo-phytodienoic acid (dnOPDA) is a 16-carbon homolog of OPDA that is synthesized from 16:3 fatty acid via a parallel hexadecanoid pathway (Weber et al, 1997;Acosta and Farmer, 2010). OPDA and dnOPDA containing galactolipids have been found in Arabidopsis, indicating that these compounds also exist in an esterified form (Stelmach et al, 2001;Hisamatsu et al, 2003Hisamatsu et al, , 2005Andersson et al, 2006;Buseman et al, 2006;Nakajyo et al, 2006;Bö ttcher and Weiler, 2007;Kourtchenko et al, 2007;Glauser et al, 2008). OPDA is transported from the plastid to the peroxisome, where CTS has been shown to be involved in its transport into the peroxisome (Theodoulou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis contains OPDA esterified to membrane lipids, classified as arabidopsides (Stelmach et al, 2001;Hisamatsu et al, 2003Hisamatsu et al, , 2005Andersson et al, 2006;Buseman et al, 2006;Nakajyo et al, 2006;Bö ttcher and Weiler, 2007;Kourtchenko et al, 2007). Arabidopsides were described to possess senescencepromoting , growth-inhibiting (Nakajyo et al, 2006), antimicrobial (Andersson et al, 2006), and antifungal (Stelmach et al, 2001;Kourtchenko et al, 2007) properties.…”
Section: Oxylipin Accumulation Induced By Gs-inherent Lipase Activitymentioning
confidence: 99%
“…It was also proposed that arabidopsides function as storage molecules for OPDA and serve as substrates for JA biosynthesis (Kourtchenko et al, 2007). It was already shown that arabidopside levels are highly induced by wounding (Stelmach et al, 2001;Buseman et al, 2006;Bö ttcher and Weiler, 2007). Dabrowska et al (2009) proposed that OPDA has a direct negative influence on herbivores; accordingly, arabidopsides may act as direct defense compounds against herbivores.…”
Section: Oxylipin Accumulation Induced By Gs-inherent Lipase Activitymentioning
confidence: 99%
“…Species-It has been reported that arabidopsides occur only in A. thaliana and Arabidopsis arenosa but not in any other plant species examined so far (38). We examined whether MGDG-oxoacids were present in cabbage (B. oleracea, Brassicaceae), tobacco (N. tabacum, Solanaceae), tomato (S. lycopersicum, Solanaceae), and common bean (P. vulgaris, Fabaceae) ( Table 3).…”
Section: Mgdg-oxoacids In Other Plantmentioning
confidence: 99%